1990
DOI: 10.1096/fasebj.4.1.2153085
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle fiber, nerve, and blood vessel breakdown in space‐flown rats

Abstract: Histochemical and ultrastructural analyses were performed postflight on hind limb skeletal muscles of rats orbited for 12.5 days aboard the unmanned Cosmos 1887 biosatellite and returned to Earth 2 days before sacrifice. The antigravity adductor longus (AL), soleus, and plantaris muscles atrophied more than the non-weight-bearing extensor digitorum longus, and slow muscle fibers were more atrophic than fast fibers. Muscle fiber segmental necrosis occurred selectively in the AL and soleus muscles; primarily, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 25 publications
8
64
0
2
Order By: Relevance
“…Exposure to microgravity or hind limb unloading of rodents causes passive shortening of soleus muscle due to ankle plantarflexion (20,39,59), which reduces the mechanical stress (20) and neural activity (19,20,39,43). Even though it is well-reported that muscles composed predominantly of slowtwitch fibers are more susceptible to unloading-related atrophy (6,41,42,(45)(46)(47)59), atrophy in soleus muscle of mice composed of fast-twitch fibers mainly was also observed in all types of mice, as was reported elsewhere (40,48,55). The unloading-related decreases in fiber length and sarcomere number may be associated with the remodeling of muscle fibers and sarcomeres, as was reported before (20,59).…”
Section: Responses To Unloadingsupporting
confidence: 54%
See 2 more Smart Citations
“…Exposure to microgravity or hind limb unloading of rodents causes passive shortening of soleus muscle due to ankle plantarflexion (20,39,59), which reduces the mechanical stress (20) and neural activity (19,20,39,43). Even though it is well-reported that muscles composed predominantly of slowtwitch fibers are more susceptible to unloading-related atrophy (6,41,42,(45)(46)(47)59), atrophy in soleus muscle of mice composed of fast-twitch fibers mainly was also observed in all types of mice, as was reported elsewhere (40,48,55). The unloading-related decreases in fiber length and sarcomere number may be associated with the remodeling of muscle fibers and sarcomeres, as was reported before (20,59).…”
Section: Responses To Unloadingsupporting
confidence: 54%
“…myonuclei; muscle fiber size; osteopetrotic mice; satellite cells; unloading and reloading SKELETAL MUSCLES ARE COMPOSED of multinucleated muscle fibers and have an extensive capacity for morphological and functional adaptation. For example, chronic unloading of muscles by bedrest in humans (45,46,64) and hind limb suspension and actual spaceflight in animals (6, 40 -42, 47, 59) result in muscle fiber atrophy and a shift toward a faster myosin heavy chain profile, particularly in antigravity muscles composed predominantly of slow-twitch fibers, such as the soleus (6,42,(45)(46)(47) and adductor longus (41, 59). Muscle fiber atrophy and the shift toward a faster myosin heavy chain profile are reversed in response to muscle reloading (41,45,46,59).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Morphological, biochemical, and functional investigations of mitochondria have clearly established the existence of organellar heterogeneity in a variety of tissues, including brain (39), liver (40 -43), heart (44 -51), and skeletal muscle (19,(52)(53)(54). Studies of skeletal muscle subject to conditions of chronic use or disuse have indicated that SS mitochondria are synthesized or degraded in more dramatic fashion than IMF mitochondria (20,(55)(56)(57). This heterogeneous response of the two mitochondrial subfractions implies that a different pattern or regulation of mitochondrial biogenesis exists in distinct regions of the muscle cell, perhaps influenced by surrounding nuclear domains (58) or the proximity to environmental factors (e.g.. PO 2 ; Ref.…”
Section: Imf and Ss Mitochondrial Protein Respond Differently To Altementioning
confidence: 99%
“…Partindo do princípio de que a complacência venosa esteja realmente aumentada 1,30 , a passagem para a postura ereta levaria imediatamente ao armazenamento de sangue nos membros inferiores, o que acentuaria a redução do retorno venoso causada pela hipovolemia. Este efeito poderia ainda ser amplificado por um aumento da permeabilidade capilar, conforme sugerido pela presença de petéquias hemorrágicas em astronautas do Skylab 1 e edema e extravasamento de hemácias de membros posteriores em ratos do projeto Cosmos 71 . No entanto, a avaliação indireta da resposta vascular ao estresse gravitacional mostrou resultados conflitantes: testes de head up tilt (o inverso de HDT) aplicados em astronautas do projeto Gemini logo após o regresso produziram aumentos de 12 a 82% no volume da panturrilha 1 ; por outro lado, astronautas recém-chegados das missões Apollo e de vôos de 6-9 dias no ônibus espacial apresentaram respectivamente diminuição ou ausência de alteração do volume da panturrilha quando submetidos ao teste de LBNP em posição supina 1,66 .…”
Section: Controle Geral Da Circulação Em 0gunclassified